Depression in diabetic foot ulcer: Associated factors and the impact of perceived social support and anxiety on depression - Polikandrioti, Maria (Int Wound J, 2020)
Diabetic foot ulcer (DFU) exerts a heavy physical and emotional burden on patients with diabetes mellitus. The purpose of the present study was to explore the impact of anxiety and perceived social support on depression of DFU patients well as patients' characteristics associated with depression. The sample of the study consisted of 180 DFU patients. Data collected by the completion of “Self‐rating Depression/Anxiety Scale‐ Zung” (SDS/SAS) and the Multidimensional Scale of Perceived Social Support (MSPSS). Patients had moderate levels of anxiety and depression (median: 36, 42, respectively) and high levels of perceived social support from their significant ones, their family and friends (median: 24, 24, 17, respectively). After multiple regression factors that were found to have an impact on depression after taking into account all other factors, were patient's age of above 70 years, patient's anxiety and the social support they received from their significant ones. More specifically, patients aged above 70 years had 9.51 points higher depression than patients aged <50 years of age (β = 9.51, 95% CI: [0.76, 18.25], P = .034). Moreover, one point increase in patient's anxiety score indicated an increase of 0.71 points in patient's depression (β = 0.71, 95% CI: [0.43, 1.00], P = .001). On the contrary, one point increase in patient's social support from their significant ones indicated a decrease of 1.52 points in patient's depression (β = −1.52, 95% CI: [−0.25, −2.79], P = .020). Clinically, a better understanding of factors having an impact on depression on DFU may provide an essential in planning cost effective interventions.